Mid to late Holocene climate variability, forest fires and floods entwined with human occupation in the upper Ganga catchment, India. (1st October 2022) - Sharma, Shubhra; Sati, S.P.; Basavaiah, N.; Pandey, Shilpa; Sundriyal, Y.P.; Rana, Naresh; Singh, Priyanka; Pradhan, Subhendu; Shukla, A.D.; Bhushan, R.; Bhatt, Rakesh; Juyal, Navin
Abstract: The present study attempts to understand the geomorphic response in the upper Ganga catchment to the mid-late Holocene (neoglacial) climate variability. The study infers five major phases of millennial-scale climate variability with centennial-scale inversions using geochemical and magnetic proxies from relict Lesser Himalayan Lake sediments. Phase-1 (6–4 ka) is marked by enhanced precipitation/runoff (increased allochthonous contribution) under a stronger Indian Summer Monsoon (ISM). The prominent reversal in the trend between ∼5 and 4 ka includes global arid events such as 4.2 ka. Phase-2 (4–2.2 ka) shows a declining precipitation/runoff (decreased allochthonous input) under declining ISM with a prominent dip after ∼3 ka. After phase-2 the climate reversals are distinct and of shorter (centennial) duration. For example, in Phase-3 (2.2–1.4 ka) improved ISM is inferred; Phase-4 (1.4–1.0 ka) is marked by a sharp decline in the ISM, and Phase-5 (<1.0 ka) includes centennial-scale events of Medieval Climate Anomaly (MCA) and the onset of Little Ice Age (LIA). The relative increase (decrease) in the concentration of geochemical and magnetic proxies is indicative of strengthened (weakened) ISM where relatively drier phases are in sync with the North Atlantic climate perturbations. We observed clustering of optically dated flood events around 6.5, 4.5, 2.6, 1.4, 0.8, and 0.4 ka which corresponds to periods of moderate ISM thus, suggesting a coupling between warm-humid monsoon and relatively dry westerlies. The relatively higher concentration of micro-charcoal in the lake sediments indicates widespread forest fires around 5.9–5.3, 4.5–4.3, 3.4–3.0, 2.0–1.5 and ∼1 ka. Given the archaeological evidence of sedentary settlements since ∼3 ka in the upper Ganga catchment, the study speculatively argues anthropogenic forcing for forest fires after 3 ka. Further, the highest probability flood phases succeed the fire events and may be indicative of enhanced vulnerability of the catchment to floods due to vegetation loss (enhanced erosion and surface runoff). Highlights: Neoglacial climate coupled with the North Atlantic climate perturbations. Accelerated anthropogenic intervention (deforestation/forest fires) after 3 ka. Flood clusters after 3 ka succeed forest fires (enhanced surface erosion/run-off).